Transport of CCL2 across an induced pluripotent stem cell-derived in vitro model of the human blood-brain barrier is heparan sulfate-dependent - Lindsey M. Williams; Takashi Fujimoto; Mamatha Damodarasamy; Riley R. Weaver; C. Dirk Keene; William A. Banks; May J. Reed; Michelle A. Erickson (PLoS ONE, 2025)
Transport of immune-active substances across the blood-brain barrier (BBB) is an important mechanism of neuroimmune regulation. CCL2 is an exemplary chemokine that regulates neuroinflammation and can cross the intact BBB from blood to brain in mice. This study aimed to characterize the blood-to-brain transport mechanisms of human CCL2 using human induced pluripotent stem cell (iPSC)-derived brain endothelial-like cells (iBECs), an in vitro BBB model. Since heparan sulfate (HS) is an important component of the in vivo BBB that regulates CCL2 transport in mice, we first assessed HS deposition in iBECs and found that HS levels increased with extended culture time. We therefore evaluated transport of radiolabeled 125 I-CCL2 and 131 I-BSA after nine days in subculture, after HS had sufficient time to accumulate. To determine the predominant transport mechanism in vitro , we evaluated whether transport of 125 I-CCL2 and 131 I-BSA was altered in the presence of an inhibitor of the chemokine receptor CCR2, and following treatment with heparin, heparinase enzymes, or the heparan sulfate synthesis inhibitor GalNaz which all test HS-dependent mechanisms of transport. We also evaluated the expression of CCR2 and membrane-bound HS proteoglycans (HSPGs) in iBECs and in isolated human brain microvessels. We found that iBECs have a functional blood-to-brain transport system for CCL2. Similar to findings in mice, heparin inhibited CCL2 transport whereas the CCR2 inhibition did not. Both heparinase treatment and treatment with GalNaz inhibited CCL2 transport across the BBB, further supporting the involvement of HS in CCL2 transport. The iBECs expressed CCR2 at levels comparable to human brain microvessels, and had detectable expression of the syndecans 1–4 and glypicans 1–6, whereas human brain microvessels expressed syndecans 2–4 and glypicans 2–5 in all subjects tested. Our findings highlight that iBECs are a useful tool for studying the involvement of heparan sulfate/glycocalyx components in the transport of substances across the BBB.